Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Ask your questions and receive precise answers from experienced professionals across different disciplines. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

What is the simplified base for the function [tex]\( f(x) = 2 \left( \sqrt[3]{27^{2x}} \right) \)[/tex]?

A. 2
B. 3
C. 9
D. 18


Sagot :

To simplify the function [tex]\( f(x) = 2\left(\sqrt[3]{27^{2x}}\right) \)[/tex], let's go through a step-by-step process:

1. Simplify the Base:
- Recall that 27 can be written as [tex]\( 3^3 \)[/tex]. So we rewrite [tex]\( 27^{2x} \)[/tex]:
[tex]\[ 27^{2x} = (3^3)^{2x} \][/tex]

2. Apply Exponent Rules:
- Using the power of a power rule [tex]\((a^m)^n = a^{m \cdot n}\)[/tex], we simplify [tex]\((3^3)^{2x}\)[/tex]:
[tex]\[ (3^3)^{2x} = 3^{3 \cdot 2x} = 3^{6x} \][/tex]

3. Simplify the Inner Function:
- Now we need to find [tex]\(\sqrt[3]{3^{6x}}\)[/tex]:
[tex]\[ \sqrt[3]{3^{6x}} = (3^{6x})^{1/3} \][/tex]
- Again, applying the power of a power rule [tex]\((a^m)^n = a^{m \cdot n}\)[/tex], we get:
[tex]\[ (3^{6x})^{1/3} = 3^{6x \cdot 1/3} = 3^{2x} \][/tex]

4. Combine the Results:
- Substituting back, we get:
[tex]\[ f(x) = 2 \left( 3^{2x} \right) \][/tex]

Therefore, the simplified base of the function [tex]\( f(x) = 2\left(\sqrt[3]{27^{2x}}\right) \)[/tex] is [tex]\(3\)[/tex].

[tex]\[ \boxed{3} \][/tex]